The Ability of Hop Extracts to Reduce the Methane Production of Methanobrevibacter ruminantium. (5th November 2021) - Blaxland, J. A.; Watkins, A. J.; Baillie, L. W. J.
Abstract : Background . Methane emissions from agriculture are responsible for over 40% of the world's greenhouse gas emissions. In the past, antibiotics were used to control methane production by animals, but concerns over the emergence and spread of antibiotic-resistant bacteria to humans have prompted a search for alternative approaches. Hops are the flowers of the hop plant Humulus lupulus . They have been used to feed cattle for many years and are known to contain antibacterial compounds, and their extracts have been shown to kill members of the Mycobacterium spp including Mycobacterium bovis, the causative agent of bovine tuberculosis as well as a number of human pathogens. In this study, hop extracts were studied for their ability to inhibit methane production from Methanobrevibacter ruminantium, a major methane-producing archaeon found in the rumen of cattle. Methods . Methanobrevibacter ruminantium M1 T (DSM 1093) was grown at 37°C for 30 days, and the amount of methane produced at different time points during this period was measured using gas chromatography. The archaeon was exposed to commercial hop extracts (tetra-hydro-iso-alpha acid and beta acid) and to aqueous hop extracts of a range of hop variants, and their effect on methane production was determined. Results . All of the extracts reduced the level of methane production of M. ruminantium over the 30-day period compared to the negative control (sterile distilled water). The commercial hop extracts were the most effective at inhibiting methane production over the course of the experiment in contrast to the aqueous extracts, which showed a gradual reduction of inhibition with time. Conclusions . Hops contain compounds which inhibit methane production. Given that hops can be safely fed to cattle, this raises the possibility of rationally designing a feed strategy which could reduce greenhouse gas emissions and protect against bovine tuberculosis. This study recommends that further research be undertaken to further identifying bioactive components from hops and their efficacy against a range of archaea.